High adherence to the Mediterranean diet and Alternative Healthy Eating Index are associated with reduced odds of metabolic syndrome and its components in participants of the ORISCAV-LUX2 study - Al Kudsee, Kinda; Vahid, Farhad; Bohn, Torsten (Frontiers in Nutrition, 2022)
Background: Metabolic syndrome (MetS) is a major risk factor for cardiometabolic complications. Certain dietary patterns play a pivotal role in improving MetS components. The aim of this investigation was to study associations between the Mediterranean Diet Score (MDS) and the Alternative Healthy Eating Index (AHEI) and the odds of MetS and its components in adults living in Luxembourg. Methods: Data from 1404 adults participating in the cross-sectional ORISCAV-LUX2 study were analyzed by a self-reported questionnaire, anthropometric measures, a food frequency questionnaire (174 items), and blood/urine samples. Results: A significant association of dietary indices and MetS was not found except when expressing MetS as a score (continuous variable, log-transformed), based on the weighting of compounds using exploratory factor analysis with the MDS (beta=-0.118, 95%CI: -0.346, -0.120) and AHEI (beta=-0.133, 95%CI:-0.059, -0.019). Fully adjusted linear regression models further showed significant inverse associations between components of MetS and MDS (all as log-transformed variables), including body mass index (BMI) (beta=-0.0068, 95%CI:-0.0100, -0.0036), waist-circumference (WC) (beta=-0.0051, 95%CI:-0.0075, -0.0027), systolic blood pressure (SBP) (beta=-0.0038, 95% CI:-0.0061, -0.0016), and diastolic blood pressure (DBP) (beta=-0.0035, 95%CI:-0.0062, -0.0009). Similarly, significant inverse associations between AHEI and components of MetS (log-transformed) included BMI (beta=-0.0010, 95%CI:-0.0016, -0.0004), WC (beta=-0.0007, 95%CI:-0.0011, -0.0003), SBP (beta=-0.0006, 95%CI:-0.0010, -0.0002), and DBP (beta=-0.0006, 95%CI:-0.0011, -0.0001). Conclusions: Higher adherence to Mediterranean diet and following healthy eating guidelines were associated with reduced odds of MetS and several of its components in Luxembourgish residents, highlighting that balanced and healthy eating patterns are a crucial cornerstone in the fight against MetS.